Back Cover Image. (19th August 2021) - Zendonadi dos Santos, Nícolas; Piepho, Hans‐Peter; Condorelli, Giuseppe Emanuele; Licieri Groli, Eder; Newcomb, Maria; Ward, Richard; Tuberosa, Roberto; Maccaferri, Marco; Fiorani, Fabio; Rascher, Uwe; Muller, Onno
Abstract : The cover image is based on the Original Article High‐throughput field phenotyping reveals genetic variation in photosynthetic traits in durum wheat under drought by Nícolas Zendonadi dos Santos et al., https://doi.org/10.1111/pce.14136 . Abstract : The cover image is based on the Original Article High‐throughput field phenotyping reveals genetic variation in photosynthetic traits in durum wheat under drought by Nícolas Zendonadi dos Santos et al., https://doi.org/10.1111/pce.14136 .